Manajemen Penanganan Covid-19: Studi Kualitatif pada Tenaga Kesehatan di Puskesmas Jember Kidul, Jember - Vio Putri Andi Lestari; Hanny Rasni; Tantut Susanto (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
Healthcare providers (HCPs) at public health centers have a huge role at the frontline, especially in preventive and promotive efforts during this COVID-19 pandemic. The purpose of this study was to analyze the management of COVID-19 among HCPs at the Jember Kidul Public Health Center (PHC) of Jember regency regarding the seventh pillar of World Health Organization (WHO) standards for the management of COVID-19 using descriptive phenomenology was performed among HCPs who handled for management of COVID-19 at PHC. Data were saturated among five of HCPs. Data were analyzed using the Colaizzi approach. The result described seven themes, including preparation of logistics, staff PHC for facing the COVID-19 pandemic, clinical management of COVID- 19 at the PHC, PHC treatment for risk and comorbid patients, Monitoring self-care at home, financing of PHC for services COVID-19, and caring for a vulnerable population. Therefore case management for the treatment of COVID-19 is vital for identifying and evaluating appropriate management for infectious disease eradication programs at PHC.